Small-sized milk processing plant considerations - Rosario, B. Macias; McVay, L.; Aramouni, Fadi M.; Schmidt, Karen A. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Milk is widely considered one of the world’s most valuable foods. As a raw material, it is available in various forms, and is found in an ever-increasing variety of nutritional products. Milk is a complex biological fluid consisting of the following components: water (87.4%), sugar or lactose (4.8%), fat (3.7%), protein (3.4%), minerals (0.7%), as well as minute amounts of vitamins. This document presents the standards, process needs, and labeling requirements of pasteurized fluid milk for the state of Kansas.
Keywords: Dairy; Raw milk standards; Processed milk standards; Processed milk equipment